Irrigation management for paddy using geographic information system - Kamal, Md. Rowshon; Kwok, Chee Yan; Lee, Teang Shui (Universiti Putra Malaysia, 1999)
Indicators and techniques of management system are important to evaluate the irrigation system. This study involves the evaluation of the management of an irrigation system spatially and temporally using Geographical Information Systems. It has great practical and application prospects, which can break down the single search method, and share graphics and databases and to present the results spatially on a map involved an efficient combination of information databases in rice irrigation system.